Spatial and Temporal Evolution Pattern of Water Conservation Function of Ningxia Province and Its Attribution Analysis - WANG Peng; MA Yilun; CHENG Jing; XU Mingxiang; SU Shengliang; PU Yong; HAN Lei; YANG Fang (Shuitu Baochi Xuebao)
［Objective］ To assess the water conservation capacity of the upper Yellow River region, and to provide a scientific basis for the ecological protection and high-quality development of the Yellow River basin. ［Methods］ Taking Ningxia Province as a case area, the spatial and temporal evolution trend of the water conservation capacity of Ningxia Province from 1990 to 2020 was calculated based on the InVEST model, the Hurst index and the geodetector model, and its key influencing factors were identified. ［Results］ The land use pattern of Ningxia Province changed significantly, except for the unused land, all other land use types showed different degrees of increasing trends. The water conservation volume of Ningxia showed an increasing trend from 1990 to 2020, with an increase of about 0.009 mm/a. The spatial distribution pattern of the water conservation capacity showed a trend of “low in the north and high in the south”, and had a significant spatial clustering characteristic. The change of water conservation function in Ningxia was not sustainable, and would face the risk of degradation in the future. Precipitation was the main factor affecting the water conservation capacity of Ningxia, followed by elevation and slope, while vegetation cover and evapotranspiration had the lowest degree of influence. ［Conclusion］ The water conservation function and its sustainability of Ningxia Province recovered during the study period, but further enhancement of water conservation capacity is still needed to cope with future risk of degradation. The results of the study can provide a scientific basis for the construction of a pioneer area for ecological protection and high-quality development in the Yellow River Basin.